Management of spontaneous coronary artery dissection in the primary percutaneous coronary intervention era. - Adlam, D; Cuculi, F; Lim, C; Banning, A (2010)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndromes. The increasing use of early angiography in the primary percutaneous coronary intervention (PPCI) era has led to earlier identification of patients with SCAD and may encourage an increased use of percutaneous revascularization strategies in this population. However, the pathophysiology of SCAD is distinct from the usually stenotic atherosclerotic plaque-rupture events responsible for most ST-elevation and non-ST-elevation myocardial infarctions, but our approach to managing these patients utilizes largely the same medical and revascularization therapies used in conventional acute coronary syndromes. This review examines the literature on SCAD and contemporary management issues.